Epidemiological analysis of tuberculosis in Brazil - Rodrigues, Alice Souza; Ohara, Elisabete Calabuig Chapina; Oliveira, Lívia Mendes; Souza, Nathália Lima (Seven Editora, 2023)
INTRODUCTION: Tuberculosis (TB) is still a major public health problem worldwide. It is estimated that in 2019, worldwide, about ten million people evolved with TB and 1.2 million died due to the disease. As for treatment outcomes, in 2018, the percentage of treatment success was 85% among new cases. OBJECTIVES: To conduct an epidemiological analysis of tuberculosis in Brazil from 2012 to 2022. METHODOLOGY: This is a bibliographic and theoretical-descriptive research, based on studies and theoretical research, seeks to identify elements to describe characteristics related to information, usability and visualization of platforms that provide open data. Data collection was performed in the following sources: Database of the Unified Health System - DATASUS and official documents of the Ministry of Health. Descriptors used for the search were tuberculosis, epidemiology, incidence, vulnerability. The time frame determined 2012- 2022. RESULTS: In the stratification by Federated Unit, there is evidence of an important heterogeneity in the country, with the highest incidence coefficients of TB in the Southeast. Men between 25 and 40 years old are the most affected by TB, a fact that may be related to the man's lifestyle. Indigenous, black and brown populations appear to be more vulnerable to tuberculosis. The prevalence of TB higher in individuals who have not completed elementary school. FINAL CONSIDERATIONS: It is concluded that the greatest representativeness of populations are the most vulnerable to TB, among new cases, which indicates that intersectoral actions will be necessary to serve vulnerable populations, in addition to articulated actions between the three spheres of management of the Unified Health System (SUS). DOI:https://doi.org/10.56238/globalhealthprespesc-045